Cinnamaldehyde Relieves Induced Hepatocellular Carcinoma in Rat Model via Targeting Wnt/β-Catenin Pathway - Al Shaima G. Abd El Salam; Yara A. Samra; Mamdouh M. El-Shishtawy (MDPI AG, 2022)
Cinnamaldehyde (CA) is a natural compound that has promising biological activity. The current study investigates the antitumor activity of CA in thioacetamide induced hepatocellular carcinoma (HCC) in rats through targeting the Wnt/β-catenin pathway and evaluates the capability of CA to relieve hepatocytes oxidative stress in the HCC-rat model. After 16 weeks of HCC induction by thioacetamide (TAA), rats were treated for 7 consecutive weeks with CA daily; i.p. injection, Alpha-fetoprotein (AFP) level, necroinflammatory score and fibrosis percentage were measured to assess HCC development. The Wnt/β-catenin pathway was evaluated by measuring the hepatic protein level of Wnt-3a, β-catenin, cyclin D, matrix metalloproteinase-9 (MMP-9), and vascular endothelial growth factor (VEGF). Furthermore, hepatocytes' oxidative stress was assessed by measuring hepatic GSH and MDA contents. Results showed that CA was significantly inhibiting the Wnt/β-catenin pathway through the downregulation of hepatic Wnt-3a, β-catenin, cyclin D, MMP-9, and VEGF. Moreover, CA ameliorates hepatocytes' oxidative stress via lowering hepatic MDA content and rising hepatic GSH content. Thus, in conclusion, CA is a promising treatment for HCC. It not only has an effective antitumor activity but also ameliorates hepatocytes' oxidative stress.